MOTIVASI DAN PERSEPSI WISATAWAN TENTANG DAYA TARIK DESTINASI TERHADAP MINAT KUNJUNGAN KEMBALI DI KOTA WISATA BATU - , Dilla Pratiyudha Sayangbatti, Dr. M. Baiquni, MA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research is done in order to find out motivation and perception about tourist destination toward eagerness of visiting back to Kota Wisata Batu. formulation of the problem in this study were : 1. What is the motivation which encourage tourist visiting Kota Batu 2. How does the perception of tourists to the attraction tourist destination Kota Batu 3. How does the motivation and tourist perceptions of the attractiveness of tourist destinations interest in a return visit in Kota Batu The method use is Random Sampling, the sampling technique that gives equal opportunities to members of the population randomly. Accidental Sampling techniques also used, namely retrieval techniques without careful planning to meet members of the population that has the same opportunities as well. Respondents of this study was the visitors who come to Kota Batu as a research site. Sample size using the formula total population is unknown (Kusmayadi dan sugiarto, 1999:74).. The spreading of the 100 questioners 56% of the male sex by age of majority 21-30 years, entrepreneur jobs, high school educational background with an average income a month is less then Rp. 750.000,- with the average tourist expenditure less than Rp. 500.000,- a large numbers of visit performed 2 times. The analysis of the highest tourist motivation is to enjoy the beauty of nature and seek new experiences. Perception about tourist destination of Kota Wisata Batu said the facilities, infrastructure and authenticity has been appropriate, but there is need for improvement in the transportation of tourists is still considered less support. The study also shows that tourist who had visited Kota Wisata Batu wanted to do return visit. This requires the government and the authority of ODTW to improve existing facilities infrastructure and maintain the authenticity of its natural attractions.